Adegan Makan dalam Film-film Roufy Nasution (Analisa Semiotika Roland Barthes) - Minfadly Robby; Yanti Heriyawati; Enok Wartika (Pascasarjana ISBI Bandung, 2022)
Roufy Nasution is a filmmaker from Bandung who has produced many audio-visual works. This article aims to explain the meaning of signs, signifiers and signified of eating scenes in films made by Roufy Nasution. Roufy Nasution’s films studied here are Jeni Lova, Elise and Unseen Foot, The Substitute Woman, A Matter of Time, and The Boy with Moving Image. The study applies a qualitative descriptive method based on Roland Barthes’ semiotic theory. This qualitative descriptive method looks at the signs of the eating scenes in Roufy Nasution’s films. The results show that the eating scenes in Roufy Nasution’s films are closed to people’s lives. The conversations coming out in the eating scenes are the emotional determinants and clues of the film’s characters. The signs-signifiers from one film to another made by Roufy are not related to one another. However, the types of shots taken by Roufy are generally similar. Roufy interprets the eating scene as a sacred moment to talk about complaints.Keywords: Semiotics, Barthes, Roufy Nasution, Food Scenes, Film